Gunn's dots as indicators of renal function, findings from the tongren health care study - Xue, Can Can; Gao, Li Qin; Cui, Jing; Zhang, Chun; Chen, Dong Ning; Wang, Ya Xing; Jonas, Jost B. (Retina, 2022)
Purpose: To investigate the prevalence of Gunn's dots (GDs) and associated systemic factors in adult Chinese. Methods: A cross-sectional study enrolling participants older than 45 years from a community-based study. Gunn's dots were evaluated using fundus photography, and associated systemic factors were analyzed. Patients with any retinal or optic neuropathy were excluded. Results: The study included 4,118 participants (mean age: 58.3 ± 9.9 years; male: 1,699/41.3%). Gunn's dots were found in 931 participants, with a prevalence of 22.6 ± 0.8% (95% confidence interval [CI]: 21.3-23.9). Systemic factors associated with a higher GD prevalence were younger age (odds ratio [OR]: 0.92; 95% CI: 0.91-0.93; P < 0.001), higher estimated glomerular filtration rate (eGFR) (OR: 1.01; 95% CI: 1.001-1.02; P = 0.022), and higher serum concentration of triglycerides (OR: 1.08; 95% CI: 1.004-1.16; P = 0.040). The GD prevalence was 3.5 (OR = 3.46; 95% CI: 1.06-11.35) and 4.4 (OR = 4.37; 95% CI: 1.27-15.09) times greater for participants with an eGFR of ≥90 mL/minute/1.73 m2 and an eGFR of ≥100 mL/minute/1.73 m2, respectively, as compared with participants with an eGFR of <60 mL/minute/1.73 m2. Conclusion: The GD prevalence (mean: 22.6%) was associated with younger age, higher eGFR, and higher serum triglyceride concentrations. The presence of GDs may serve as indicators of healthy renal function.